2007
DOI: 10.1111/j.1348-0421.2007.tb03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Efficient Virological Response to Pegylated Interferon/Ribavirin Combination Therapy by NS5A Sequences of Hepatitis C Virus and Anti‐NS5A Antibodies in Pre‐Treatment Sera

Abstract: A considerable number of patients infected with Hepatitis C virus subtype 1b (HCV‐1b) do not respond to pegylated interferon/ribavirin combination therapy. In this study we explored a useful factor(s) to predict treatment outcome. A total of 47 HCV‐1b‐infected patients were treated with pegylated interferon/ribavirin for 48 weeks. Sera of the patients were examined for the entire NS5A sequence of the HCV genome, HCV RNA titers and anti‐NS5A antibodies. According to their responses, the patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…Akuta et al [15] reported that mutations of amino acids in the core protein region (core 70 and 91) were significantly associated with a non-response to combination therapy. Subsequently, a specific region other than the ISDR (NS5A 2334-2379) was found to be related to the treatment response to IFN-α plus RBV therapy, and was reported as the Interferon/Ribavirin Resistance-Determining Region (IRRDR) [16,17] . Overall, the most important viral factors associated with the response to IFN-α treatment for HCV were determined to be the amino acid sequences in the core region and NS5A region, such as mutations of core 70, core 91, ISDR and IRRDR.…”
Section: Ifn Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Akuta et al [15] reported that mutations of amino acids in the core protein region (core 70 and 91) were significantly associated with a non-response to combination therapy. Subsequently, a specific region other than the ISDR (NS5A 2334-2379) was found to be related to the treatment response to IFN-α plus RBV therapy, and was reported as the Interferon/Ribavirin Resistance-Determining Region (IRRDR) [16,17] . Overall, the most important viral factors associated with the response to IFN-α treatment for HCV were determined to be the amino acid sequences in the core region and NS5A region, such as mutations of core 70, core 91, ISDR and IRRDR.…”
Section: Ifn Treatmentmentioning
confidence: 99%
“…70 and 91) Mutations of amino acids were associated with a poor response to IFN-α plus RBV treatment [15] IRRDR Mutations of the IRRDR (NS5A 2334-2379) were associated with a favorable response to the IFN-α plus RBV treatment [16,17] Drug resistant mutation associated with the response to IFN treatment for HCV infection. In addition, viral mutations resistant to DAAs have become problematic in recent triple therapies.…”
Section: Anti-ifn Neutralizing Antibodies In Peg-ifn-α Treatment Withmentioning
confidence: 99%
“…Markers may be based on viral factors, such as viral sequence variation (3); host factors, such as gene expression profiles (4) or polymorphisms in specific host genes (5); or combinations thereof (6,7). Interestingly, very different types of biomarkers can give similar results, indicative of the intimate interactions between the manifold host and viral players in virus replication and disease progression.…”
mentioning
confidence: 79%
“…Presently, therefore, prediction of the effectiveness of treatment of chronic hepatitis C before its initiation is considered extremely important, and many predictive factors of the effect of treatment have been reported. Among them, gene mutations and polymorphisms in the virus and host have been suggested to be factors that markedly affect the sensitivity to INF (12)(13)(14)(15)(16)(17)(18). Particularly, it has been considered difficult to achieve SVR in a patient showing the progres- Figure 2.…”
Section: Discussionmentioning
confidence: 99%